The Designing of Interactive Learning Media at Yogyakarta’s Sandi Museum Based on Augmented Reality - Prita Haryani; Joko Triyono (JOIV : International Journal on Informatics Visualization, 2020)
Sandi Museum is one of museums that exhibits various collections of historical code in the forms of realia, replica, machine, picture and document related to codes. As the information  sources of national cultural wealth, the existence of Sandi museum has not been visited by the tourists yet. It is because of the lack of museum promotion to community. Besides that, there is a stigma of community that museum is only the place to store the historical goods, therefore, the community activities when visiting the museum tend to be passive, in which they only look around the collections of historical goods without any interactions happened in visiting the museum. In order to get attraction of tourists when they are visiting the Sandi museum, the museum’s officials are able to use the interactive learning media based on the technology of Augmented Reality in introducing Sandi museum. The visitors  are able to visualize the object or historical good in 3 dimension (3-D) which is real time. The museum introduction based on  Augmented Reality  enables visitors to be able to interact with the objects or the historical goods through intuitive and interesting way. In this research, it is going to make AR-Sandi application as the information media to introduce Sandi museum to the community. The research approach used is research and development approach with the development model of waterfall. The Model of waterfall  consists of five phases, namely analysis, design, implementation, testing and maintenance. The result of the research is that the application of  AR-Sandi has been successfully developed in accordance to the methodology of waterfall. Based on the acceptance testing of  AR-Sandi application with the framework of TAM (Technology Acceptance Method) towards 30 visitors of Sandi museum, it is obtained that the majority of visitors agrees, the AR-Sandi application is acceptable by the users, it has functionality and work performance well.